Talent management : a decade of developments - Collings, David G.; Vaiman, Vlad, 1971-; Scullion, Hugh (Talent management., 2022)
This book contains an Open Access chapter. Over the past two decades, the field of talent management has established itself as a key area of management practice and research. Emerging from the practitioner literature in the 1990s, the research evidence bases truly materialised in the late 2000s onwards. The launch of the EIASM Workshop on Talent Management in 2012 coincided with this surge in research interest, and we are now in a critical time in the evolution of our understanding of talent management. Talent Management: A Decade of Developments presents valuables insights into the progression in the critical understanding of talent management, building upon a decade of the EIASM Workshops. Bringing together leading voices in talent management research to reflect on recent developments and the current state of research, examining key issues such as talent philosophies, star performers, talent turnover and retention. Aimed at researchers, postgraduate students, and professionals in the field, this collection features the leading experts in their respective areas within talent management. Talent Management: A Decade of Developments charts the evolution of talent management, illustrating the progress, prospects, and challenges that have transpired over the last ten years.